Mixing in the mechanically agitated bioreactor: ‘A matter of being stirred, not shaken’ - Shaliza, Ibrahim, Prof. (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/